Fresno County Bar Association's 110th Annual Bar Banquet Held At Elks Lodge - Watkins, Howard::::::::: (1982)
Judge James V. Paige in costume kissing Judge Sandra Snyder playing Princess Laya; Judge James Ardaiz laughing wearing full white wig 5080 E. Kings Canyon Road, Fresno